IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE (GCG) PRINCIPLES IN THE IMPLEMENTATION OF THE PARTNERSHIP PROGRAM IN THE COMMUNITY DEVELOPMENT CENTER (CDC) UNIT OF PT TELKOM TBK IN PANGKALPINANG CITY - tiara ramadhani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jember)
IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE (GCG) PRINCIPLES IN THE IMPLEMENTATION OF THE PARTNERSHIP PROGRAM IN THE COMMUNITY DEVELOPMENT CENTER (CDC) UNIT OF PT TELKOM TBK IN PANGKALPINANG CITY Tiara Ramadhani Faculty of Social and Political Science Bangka Belitung University tiaramadhani30@yahoo.co.id ABSTRACT The implementation of the partnership program by State-Owned Enterprises (SOEs) aims to improve the social welfare of small and medium-sized businesses (MSMEs). Social welfare in question is a condition of fulfilling the social and economic life of small and medium-sized businesses in order to become resilient and independent and be able to function socially. However, before the program can meet the objectives of social welfare, it is necessary to consider whether in implementing the program, it has applied the principles of Good Corporate Governance (GCG). In short, this is what underlies the writing of this journal. This journal aims to describe